Financing the future: insights into sustainable energy investments through scientific mapping and meta-analysis - Mustafa Raza Rabbani; Madiha Kiran; Zakir Hossen Shaikh (Discover Sustainability)
Abstract This study presents a detailed literature review on financing for renewable and sustainable energy through bibliometric analysis and scientific mapping, utilizing the Scopus database from 2000 to 2023. Using network analysis techniques, it identifies eight main clusters, each focusing on different aspects of financing renewable energy and their geographic and technical contexts. The study highlights the most frequently cited articles, notable authors, key institutions, affiliations, and journals in sustainable energy finance. A random effects model meta-analysis was also conducted to assess the overall effect size of each research stream. Findings indicate that the literature on renewable energy finance has expanded since 2000 and exhibits considerable diversity. The study pinpoints five major themes suitable for discussion and exploration of new research questions: (i) the role of Fintech in renewable energy finance, (ii) the regulatory framework governing renewable energy finance, (iii) the economic feasibility of renewable energy in emerging markets, (iv) the influence of private and public finance on renewable energy development, and (v) the relationship between renewable energy finance and sustainable development goals. The insights from this study aim to inspire and equip readers as they embark on their inquiries into the connections between energy investment, policy, finance, and behavioral sciences. Following identifying research gaps, this paper outlines potential future research directions. It serves as a thorough resource on current trends in sustainable energy investments and recommends viable research topics, thus benefiting researchers, professionals, and policymakers alike.